The Attacks on the Critical Infrastructure of Pakistan: Editorial - Zuberi, Kaukab Jamal (International Journal for Electronic Crime Investigation, 2021)
It’s the broadband networks beneath us and the wireless signals around us, the local networks in our schools and hospitals and businesses, and the massive grids that power our nation. It’s the classified military and intelligence networks that keep us safe, and the World Wide Web that has made us more interconnected than at any time in human history